On the Secular State: A Response to Mohamad Amer Meziane - Asad, Talal (Political theology, 2021)
This essay deploys a reflection on the secular state and the forms of violence that constitutes it. It formulates several comments about its sovereignty as well as the distinction between about morality and politics. It then responds to several critical questions and crucial arguments made by Mohamad Amer Meziane in his innovative essay on The Deafness of the State. Its conclusion particularly responds to different themes formulated in Meziane's essay such as the status of the voice in Islam, the nature of modern sovereignty and the relation between decolonization and the state.